Freedom in Margaret Atwood's novel The Handmaid's Tale - Cheong, Pui Yin; Wan Yahya, Wan Roselezam (Scottish Group, 2013)
The two different eras in The Handmaid’s Tale can be seen and framed in terms of two opposing types of freedom that Isaiah Berlin proposed, i.e. negative and positive freedom. While one may automatically contend that the situation in the dystopian setting of the Gileadean era is worse than the pre-Gileadean, it is necessary for readers to study closely if this is the case. The individual freedom to choose during the pre-Gileadean era indicates that this freedom pertains mostly to an individual’s desire as opposed to the society at large. During the Gileadean era, on the other hand, freedom is seen as a form of collective decision, to curb individual desires to achieve 'true' freedom, as aspired to by the rigid, moral, social rules and regulations of a good citizen. Read in relation to Berlin’s idea of freedom, the results show the contrary, that the pre-Gileadean era practises negative freedom while during the Gileadean era positive freedom is exercised. This is an alarming result, especially when individual freedom seems to be valorised and upheld in a modern, pre-Gileadean society, while individual freedom is totally curbed in the traditional society of the Gileadean era. However, it is fair to conclude that Atwood is not in favour of one freedom type over the other because freedom may be viewed as being on a continuum, where there is a middle ground with a fair mix of negative and positive freedom, because one cannot exist without the other.